Culture, meaning and language in intercultural political-postcolonial translation communication (2022)
This study contextualises translation as intercultural political textual communication and relations within the Postcolony. The Postcolony is a politically active space in which ex-coloniser and ex-colonised cultures negotiate their differentiated meanings, identities and humanities in asymmetrical relations using various communicative media including textual, oral and symbolic. Translation is both textual and symbolic communication mediated through translator-manipulable language and embossed with the potency of cultural knowledge, meaning, and identity representations, and of creating understanding or exacerbating conflict. Designed on qualitative and interpretive research and deploying postcolonial translation theory to account for inequality and contestation of knowledge and meanings in textual cultural encounters and to interrogate neocolonial forms of representation, this study heuristically reviewed the bondedness of culture, meaning and language. It further explored with illustrations from purposively selected translation text units the underlayered texture of a dialogic discourse in a postcolonial translation communication that insists on retaining and legitimizing in the target text remnants of the negative ‘otherness’ inscribed on African cultures in primordial European narratives on and attitudes towards Africa(ns). The study concluded on the critical positioning of the translator to mediate unbiased textual representation of cultural realities and identities in international cultural political communication and thus contribute to intercultural understanding and, perhaps, to intercultural cooperation.